Serious game for teaching statistics in higher education: storyboard design - Barbosa, Tiago (2019)
Serious games can be used as a way to transmit knowledge to the users/students, playing the role of a pedagogical tool in their learning process. Following this idea, a serious game on Statistics is developed for higher education level, promoting and demonstrating the applicability of statistics concepts in day-to-day life and in the decision-making process. The proposed idea is to create a challenging environment (mystery that needs to be solved), where the clues are contextualized in the statistics area through the practice of probability knowledge, confidence intervals and hypotheses tests. According to the student’s answers and choices, the game branches out leading the player to different activities/challenges, guaranteeing that, by the end of the game, the student has a better understanding of the subject. In the present paper, the storyboard and the student competencies are presented and discussed, focusing on the project’s main objectives.